Do stiffness characteristics influence change of direction ability in badminton players? - Zhihai, W.; Mingming, Y.; Kaiyuan, Q.; Xinyu, M.; Xin, Y.; Jiayu, Z.; Xiaowen, C.; Yu, C.; Anqi, L.; Dan, W. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Change of direction (COD) ability is a key predictor of athletic performance in badminton players [1], and stiffness may be one of the important factors affecting COD ability in badminton players [2-3]. The objective of this study was to investigate whether stiffness characteristics could influence the COD performance.